Anion-directed assembly of helical copper(ii) complexes based on a bispyridylpyrrole ligand: synthesis, structural and magnetic properties1. Issue 12 (11th February 2015) - Fang, Wen-Zhong; Wang, Ya-Ping; Wang, Yi-Fan; Zhang, Shou-Chun; Yi, Xiao-Yi
<x xml:space="preserve">Abstract</x> Helical copper(ii) complexes based on a bispyridylpyrrole ligand, namely the helical polymer {[Cu2(PDPH)2(N3)2]}n, a discrete double-helical complex [Cu2(PDPH)2(NO3)2] and triple-helical complex [Cu2(PDPH)3](OTf), were synthesized by displacement of Cl− in [Cu(PDPH)Cl].